Development of Android-Based Edutainment Mathematics Learning Media on Ellipse Material - Tuwuh Dwi Putra Wardana; Rooselyna Ekawati (MATHEdunesa, 2022)
Learning media is a learning aid that act as an intermediary in conveying instructional information which are one of the instruments that determine the success of learning process. The research aim is to produce an edutainment mathematics learning media based android on ellipse materials that is good and decent that can be used in the learning process. The media was developed to attract students' interest in ellipse which is considered difficult by some students The qualification of the media cover three aspects of validity, practical, and effective. This research is developed using ADDIE model which consists of analysis, design, development, implementation, and evaluation. The developed media was conducted with limited trials with the research subjects are grade XI students of SMAN 1 Kedungwaru. The instrument used on this research are validation sheets, questionnaires test of practicality, and students test. Based on the data obtained the result of validity test from the experts stated that the media was categorized as valid, from the questionnaires test of practicality from students the media was categorized as practical, and from the student test result showed that 80% of the students met the completeness limit so the media categorized as effective. The result concluded that the developed media categorized as decent and can be used in learning process. Keywords: ADDIE, android, edutainment, ellips, development, learning media